2010
DOI: 10.1159/000320853
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Degree of Left Subclavian Artery Stenosis and the Left Vertebral Artery Waveform by Pulse Doppler Ultrasonography

Abstract: Background:Development of retrograde blood flow may be observed in the vertebral artery and is associated with progressive ipsilateral proximal subclavian or innominate artery stenosis. The subclavian steal phenomenon is more prevalent in the left subclavian artery (LSA). The purpose of this study was to analyze the correlation between the degree of LSA stenosis and pulse Doppler waveforms of the left vertebral artery (LVA). Methods:A retrospective analysis of LVA waveforms was performed in 22 cases with LSA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 12 publications
(10 reference statements)
1
12
1
Order By: Relevance
“…However, in this study, 92% of patients with severe SA stenosis had type IV or V waveforms. Results from the present study also revealed that all of the patients with SA occlusion had type IV and V waveforms, which is not consistent with a previous report (Sakima et al 2011). In the present study, type IV waveforms represented 70%-89% left SA stenosis, but type V waveforms indicated SA occlusion.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, in this study, 92% of patients with severe SA stenosis had type IV or V waveforms. Results from the present study also revealed that all of the patients with SA occlusion had type IV and V waveforms, which is not consistent with a previous report (Sakima et al 2011). In the present study, type IV waveforms represented 70%-89% left SA stenosis, but type V waveforms indicated SA occlusion.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study reconfirmed that the degree of proximal SA stenosis is correlated with the ipsilateral VA waveform (Kliewer et al 2000;Sakima et al 2011;Von Reutern and Pourcelotl 1978). However, compared with the previous report, our study had five VA waveform patterns, was not limited to an evaluation of left SA stenosis, and had a relatively larger sample size.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…3 Usually, hemodynamically significant (50%-60% or higher) stenosis of the proximal SA leads to the development of SSS. 4,5 Depending on the severity of SA stenosis, there are different variants of abnormal Doppler waveforms in the affected VA ( Figure 9). 4,6 Occult subclavian steal (the affected side's VA Doppler waveforms demonstrate antegrade flow with mid-systolic notch-the "bunny sign") corresponds to the milder form of hemodynamically significant SA stenosis, partial subclavian steal (alternating "to-and-fro" waveforms) corresponds to the moderate form, and complete steal (retrograde flow in the VA) is observed in severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…VA waveforms were classifi ed in fi ve subtypes as described elsewhere [13]. Type I: normal antegrade waveform …”
Section: Methodsmentioning
confidence: 99%